Cognitive or daily stress association with headache and pain induction in migraine and tension-type headache patients: a systematic review. (4th March 2022) - Viero, Fernanda Tibolla; Rodrigues, Patrícia; Trevisan, Gabriela
ABSTRACT: Introduction: Primary headache disorders, such as migraine and tension-type headache (TTH), represent a significant public health concern. Besides, cognitive/mental stress was suggested to contribute to TTH and migraine physiopathology. Thus, this study aimed to evaluate the existence of a causal relationship between stress (mental/cognitive or daily stress) and headache or pain improvement in migraine and TTH patients. Areas Covered: We developed a systematic review of the literature, including studies that utilized mental/cognitive stress tasks or daily stress by lifestyle questionnaire in migraine and TTH patients. Necessarily, these studies should have healthy patients and a pain measure (quantitative sensory tests or headache/migraine detection). PubMed, EMBASE, and SCOPUS were searched, using terms about stress and primary headaches. Expert opinion: Both mental/cognitive stress and daily stress (perceived) were related to an increase in pain perception and related to the development of headache or enhanced transient pain intensity in migraine and TTH patients. Different factors could enrich the comprehension of the influence of stress on pain/headache induction in migraine and TTH patients, including methodological standardization, consistency of assessing, and isolating the many headache triggers in randomized controlled trial studies.